Analysis of DNA Polymerases II and III in Mutants of Escherichia coli Thermosensitive for DNA Synthesis - Gefter, Malcolm L. (1971)
A series of double mutants carrying one of the thermosensitive mutations for DNA synthesis (dnaA, B, C, D, E, F, and G) and the polA1 mutation of DeLucia and Cairns, were constructed. Enzyme activities of DNA Polymerases II and III were measured in each mutant. DNA Polymerase II activity was normal in all strains tested. DNA Polymerase III activity is thermosensitive specifically in those strains having thermoscnsitive mutations at the dnaE locus. From these results we conclude that DNA Polymerases II and III are independent enzymes and that DNA Polymerase III is an enzyme required for DNA replication in Escherichia coli.